Indonesian Students’ Learning Style in English Speaking Skill - Arjulayana Arjulayana (Universitas Muhammadiyah Tangerang, 2017)
The purpose of this research is to report the data analysis about the kinds of students’ learning style which is used by the Indonesian students in their speaking English skill. The research was conducted through qualitative descriptive research method and supported by data questionnaire. This research can be given understanding about three kinds of learning style which is able to use as a unique technique in teaching English speaking skill and the research findings show that English speaking skill can be learned by all various learner regarding with their learning style. Learning style also can be used as a teacher’s guideline to gain the objectives of study effectively, because the teacher can match their classroom strategy and method regard to students’ learning style. Based on the questionnaire data the most suitable learning style in student speaking skill is auditory learner, because auditory learners absorb the information through hearing, while hearing is the most effective way to add vocabulary, pronounce the words and getting the information clearly and effectively. Keywords: learning style, speaking skill, speaking.